Frequency of Diabetes Mellitus in Liver Cirrhosis Patients at Tertiary Care Hospital - Imran Qadir Khattak, Rubaba Khan, Romana Bibi, Javeria Anjum, Kanza Rafi, Nazir Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes mellitus is a metabolic condition comprising of irregularly elevated level blood glucose. There are several different types of Diabetes mellitus. Several studies show the association between Diabetes mellitus and liver cirrhosis. Aim: To assess the frequency of diabetes mellitus in liver cirrhosis patients at tertiary care hospital Methodology: Our study was descriptive Cross-Sectional Study carried out at the Department of Medicine, Lady Reading Hospital, Peshawar for duration of one year from 08-11-2021—08-05-2022. The detailed medical history and physical examination, demographic detail of the patients such as age, gender, and address were recorded. The data entry and analysis was done by using IBM SPSS version 23. Results: This study was conducted on 144 patients presenting with liver cirrhosis. The mean age of patients was 49.73±13.26 years. The frequency of diabetes mellitus in liver cirrhosis patients in our study was 20 (13.9%) Conclusion: Our study concludes that the frequency of diabetes mellitus in patients with liver cirrhosis is high. To validate and identify the true effect of this co-morbidity in the Pakistani community, additional prospective studies with larger populations that examine the incidence of liver deterioration in diabetic patients are required. Keywords: Liver cirrhosis, Diabetes mellitus, Insulin resistance,Endocrinopathies,